2015
DOI: 10.1101/gr.194118.115
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental control of host-gut microbiota interactions

Abstract: Genetics provides a potentially powerful approach to dissect host-gut microbiota interactions. Toward this end, we profiled gut microbiota using 16s rRNA gene sequencing in a panel of 110 diverse inbred strains of mice. This panel has previously been studied for a wide range of metabolic traits and can be used for high-resolution association mapping. Using a SNPbased approach with a linear mixed model, we estimated the heritability of microbiota composition. We conclude that, in a controlled environment, the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
262
4
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 304 publications
(284 citation statements)
references
References 65 publications
15
262
4
3
Order By: Relevance
“…Among humans, despite high inter-individual variation in the composition and structure of gut microbiota, microbial community signatures are still generally evident at the level of family households and even nations (Turnbaugh et al, 2009;Lee et al, 2011;Yatsunenko et al, 2012;Goodrich et al, 2014). These patterns could be due to either variation in shared environments or genetic relatedness (Spor et al, 2011;Goodrich et al, 2014;Org et al, 2015). Most available data suggest a strong environmental component in shaping the human gut microbiota: cohabiting parents have more similar gut microbiota than do men and women not living together (Yatsunenko et al, 2012), and monozygotic and dizygotic twin pairs generally have gut microbiota that differ to similar degrees (Turnbaugh et al, 2009;Lee et al, 2011;Yatsunenko et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among humans, despite high inter-individual variation in the composition and structure of gut microbiota, microbial community signatures are still generally evident at the level of family households and even nations (Turnbaugh et al, 2009;Lee et al, 2011;Yatsunenko et al, 2012;Goodrich et al, 2014). These patterns could be due to either variation in shared environments or genetic relatedness (Spor et al, 2011;Goodrich et al, 2014;Org et al, 2015). Most available data suggest a strong environmental component in shaping the human gut microbiota: cohabiting parents have more similar gut microbiota than do men and women not living together (Yatsunenko et al, 2012), and monozygotic and dizygotic twin pairs generally have gut microbiota that differ to similar degrees (Turnbaugh et al, 2009;Lee et al, 2011;Yatsunenko et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nest-specific microbial and volatile odor profiles could reflect influences of shared environments and/or genetic relatedness, and teasing these influences apart is one of the most pressing lines of inquiry in host microbial ecology (Spor et al, 2011;Goodrich et al, 2014;Org et al, 2015). Dark-eyed juncos afford an opportunity to do so because they are socially monogamous yet exhibit appreciable levels of extra-pair paternity (Ketterson et al, 1998;Gerlach et al, 2012a,b;Atwell et al, 2014), and although they biparentally provision their offspring, only mothers brood the eggs and nestlings (Nolan et al, 2002).…”
Section: Effects Of Social Environment and Genetic Relatednessmentioning
confidence: 99%
See 1 more Smart Citation
“…The data set contains 6138 probes and 2956 genotyped loci in 112 segregants. In addition, we evaluated our method using a gut microbiome data set (Org et al 2015) collected from 592 mice representing 110 HMDP strains. The study protocol has been described in detail by Parks et al (2013).…”
Section: Real Data Setsmentioning
confidence: 99%
“…Performing a multiple-phenotypes analysis with microbiome data may produce results that allow more complete reconstruction of these networks. We applied the standard ttest, EMMA (Kang et al 2008), MDMR (Zapala and Schork 2012), and GAMMA on a gut microbiome data set (Org et al 2015) from HMDP that contains 26 common genus-level taxa identified from 592 mice samples, including 197,885 SNPs.…”
Section: Gamma Identifies Variants Associated With a Gut Microbiomementioning
confidence: 99%